ATENSI ANAK TENTANG MENYIMAK(BICARA) PADA SISWA TAMAN KANAK-KANAK TK BHAYANGKARI KOTA TERNATE - Umikalsum Arfa (Jurnal Ilmiah Cahaya Paud, 2015)
Some problems were faced childreen in attention especially speaking competence because no confindence and spoil. If children want to speak they showed overly emotional, nervous, silent and more spoild. From those problems researher wants to find about children competences in listening and speaking. The methods children language learning can use Child direct speech. monthere, recasting, enchoing, expanding, and labeling.